Um chute no balde: o rock experimental e a vanguarda na música dos Beatles - Alves, Miguel Fabrício de Oliveira (2018)
After finally leaving the tour in 1966 at a time when his career reached high levels of public and market, thus causing a certain break with the parameters of the cultural industry, the Beatles began to concentrate their work in the studio producing what the critic considers as their more important works, evidencing a maturation that would show itself from his compositions and arrangements. Such compositions become more complex, representing their passage from commercial pop music to more elaborate, experimental and avant-garde music, exposing influences to various musical currents and references to their experiences with LSD. It is the purpose of this study to analyze the context in which these changes occurred, the relationship of the Beatles to their time, psychedelia, oriental mysticism and avant-garde rock sections.